REDESAIN MA'HAD BAKKAH MARTAPURA DENGAN PENDEKATAN ARSITEKTUR PERILAKU - Aji, Na'im Royyani; Dahliani, Dahliani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Ma'had Bakkah is a Salafi boarding school in Martapura that has grown organically sporadically following the need for space and land acquisition. Sporadic developments resulted in the inefficient arrangement of building masses and counterproductive circulation of the daily activities of students so the area needed to be redesigned. The redesign of Ma'had Bakkah uses a post-occupancy evaluation method by making student behavior the main study. The initial stage of post-occupancy evaluation is to collect data on existing assets and behavior on a macro and micro basis. The data obtained are the existing site, function, form, and the counterproductive level of the existing circulation based on three variables; steps, duration (seconds), and lines of reading the Qur'an. The set data was analyzed to produce the concept of the site, function, form, and value of the existing efficiency of Ma'had Bakkah. The results are redesigned concepts on-site, function, and form with the acquisition of post-redesigned circulation efficiency of 48% of the pre-redesigned circulation in the variable meter, steps, duration (seconds), and lines of reading the Qur'an.